The dynamic nature of community gardens through history: A literature review - Salters, Miranda; Gonsalves, Julian; Monville-Oro, Emilita; Santos-Anunciado, Ma. Shiela; Hunter, Danny (2024)
Around the globe, rapid urbanization has created challenges in ensuring access to nutritious and affordable food, as well as protecting green spaces (Guitart et al., 2012). Community gardens have emerged as dynamic spaces that address these issues while offering promising outlooks for the future of food security and sustainable urban development (Burt et al., 2020; Guitart et al., 2012). Since their inception, community gardens have undergone significant evolution. Today, they are regarded as epicenters for building community capacity, inspiring sustainable food systems, and facilitating social empowerment. However, community and allotment gardens originated as mitigation strategies during times of crisis, rather than as innovative, sustainable solutions for enhancing urban and peri-urban landscapes (Birky, 2009). This literature review aims to highlight the importance of community gardens in urban and peri-urban spaces by examining their roles in food sovereignty, community empowerment, social protection mechanisms, and humanitarian work. It does so by analyzing the literature on the origins, development, and current status of community gardens worldwide.